2016
DOI: 10.1002/oti.1445
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Individualized Occupational Therapy Programme and its Effects on the Neurocognition, Symptoms and Social Functioning of Patients with Schizophrenia

Abstract: We described an individualized occupational therapy (IOT) programme and examined the effects of adding IOT to group OT (GOT) on improving neurocognition, symptoms and social functioning among recently hospitalized patients with schizophrenia. The Brief Assessment of Cognition in Schizophrenia-Japanese version (BACS-J), the Positive and Negative Syndrome Scale (PANSS) and the Global Assessment of Functioning scale were used for outcome evaluations. Fifty-one patients were voluntarily assigned to either the GOT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
3
20
0
2
Order By: Relevance
“…The OT intervention methods administered to the participants were reported in our previous studies; we only describe the primary features here. A comparison of features between IOT and GOT is shown in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OT intervention methods administered to the participants were reported in our previous studies; we only describe the primary features here. A comparison of features between IOT and GOT is shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Takeshi Shimada, OTR, PhD, 1,2 Manami Ohori, OTR, 3 Yusuke Inagaki, OTR, 4 Yuko Shimooka, OTR, 5 Ikuyo Ishihara, OTR, 6 Naoya Sugimura, OTR, MHS, 7 Sachie Tanaka, OTR, PhD 1 and Masayoshi Kobayashi, OTR, PhD 1 * Aim: We examined the effect of individualized occupational therapy (IOT) compared to the usual group occupational therapy (GOT) on the rehospitalization of patients with schizophrenia.…”
mentioning
confidence: 99%
“…Findings of these studies demonstrated that adding IOT to GOT resulted in significant improvements in cognition and intrinsic motivation [2] and could prolong the time to rehospitalization and reduce the risk of rehospitalization in comparison to GOT alone, in addition to supporting good cognition at discharge and favorable medication adherence [3]. Details of the IOT study have been published [1][2][3].…”
Section: Cost-effectiveness Of Individualized Occupational Therapy Fomentioning
confidence: 99%
“…The OT intervention methods have been reported elsewhere [1][2][3]. We only describe the main features here.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation